Karakteristik Pantai Pulau Karimunjawa Sebagai Alternatif Lokasi Uji Terbang Pesawat N219A - Tjahjono Prijambodo; Khusnul Setia Wardani; Wahyu Hendriyono; Aris Subarkah (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
The N219 Amphibious Aircraft is an aircraft that, under certain conditions, can land on land and in water. The N219A Aircraft Development team is developing the aircraft. A flight test is at the end of this process. The condition of water being calm and protected against significant waves is one of the criteria for the selection of a position for the flight test. This paper provides an overview of the coastal zone, including waters and land on the N219 Amphibious Flight Test, Karimunjawa Island, Jepara Regency, Central Java. Identification of aircraft flight test infrastructure needs derived from several air navigability and flight security regulations. In addition, analysis is conducted on the features of the waters including: wave conditions, wind direction and magnitude, wave direction and waves height, current direction and speed, and the bathymetric conditions derived from reliable data. In furthermore, the software used in the analysis of hydro-oceanographic conditions in western-east moonsoons was used to carry out mathematical modelling. The flight test facilities of the N219A include water facilities such as take-off/landing routes, turning basin facilities and land facilities which include hangars and supporting facilities. For the purpose of the flight test the layout plan for water and land facilities is adjusted to comply with the requirements and characteristics of the Karimunjawa Island coastal area